2019
DOI: 10.1111/1750-3841.14912
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Gut Microbiota Composition and Traditional Spontaneous Fermented Dairy Foods Among Kazakh Nomads in Xinjiang, China

Abstract: The human gastrointestinal tract represents one of the most densely populated microbial ecosystems studied to date. Although this microbial consortium has been recognized to have a crucial impact on human health, its precise composition is still subject to intense investigation, as people from different regions have different gut microbiota structures. The Kazakh nomads in Xinjiang, China still retain their nomadic lifestyle and traditional diet. Their specific diet style and ancient genetic background shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The majority of fermented foods were represented by dairy products (88)(89)(90), especially fermented milk (91)(92)(93), yogurt (94)(95)(96), and different cheese varieties (97). Other fermented foods included plant and vegetable based (15,98), fermented rice (99), and diverse home-made (100) and local (101)(102)(103) fermented products. The amount of ingested fermented foods varied between 135 and 400 g/day, although not all articles reported this information, and when reported, the information was based on food frequency questionnaire (FFQ).…”
Section: Food Matrices and Microbial Compositionmentioning
confidence: 99%
“…The majority of fermented foods were represented by dairy products (88)(89)(90), especially fermented milk (91)(92)(93), yogurt (94)(95)(96), and different cheese varieties (97). Other fermented foods included plant and vegetable based (15,98), fermented rice (99), and diverse home-made (100) and local (101)(102)(103) fermented products. The amount of ingested fermented foods varied between 135 and 400 g/day, although not all articles reported this information, and when reported, the information was based on food frequency questionnaire (FFQ).…”
Section: Food Matrices and Microbial Compositionmentioning
confidence: 99%
“…Due to the production of chemokines, cytokines, growth factors, or immunoglobulins, MALT acts as a microbial fighter. Furthermore, probiotics influence the balance of the gut microbiome composition, reducing the risk of disease gut ( Tokarz-Deptuła and Deptuła, 2017 ; Azad et al, 2018 ; Li et al, 2019 ; Uusitupa et al, 2020 ; Zhang et al, 2021 ). As microbes are able to produce neurochemicals, as well as respond to them, they can play a crucial role in the treatment of depressive and anxiety disorders ( Romijn et al, 2017 ).…”
Section: Benefitsmentioning
confidence: 99%
“…(3) Xinjiang is located in northwestern of China, at the crossroads of Central and West Asia, and is a region of multi-ethnic coexistence, which avoids the bias that studying a particular ethnic group bring to the results. In the Xinjiang region, various ethnic groups develop different dietary habits as and lifestyle ( Li et al, 2019 ), distinct from the inland provinces of China. Studies have found that special dietary patterns and lifestyles in the Xinjiang region influence the prevalence of metabolic syndrome and its components ( Zhang et al, 2024 ; Hailili et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%